Cyrtodactylus samroiyot, a new limestone-dwelling Bent-toed Gecko (Squamata: Gekkonidae) from Prachuap Khiri Khan Province, peninsular Thailand - Pauwels, Olivier S. G.; Sumontha, Montri (Zootaxa, 2014)
We describe Cyrtodactylus samroiyot sp. nov. from a limestone relief in Sam Roi Yot District, Prachuap Khiri Khan Province, peninsular Thailand. It is characterized by a maximal known SVL of 66.9 mm; 17–18 longitudinal rows of dorsal tubercles; 33–34 longitudinal rows of ventrals across the abdomen between the ventrolateral skin folds; a continuous series of seven precloacal pores in males (six shallow precloacal pits in females); a series of slightly enlarged, poreless and pitless femoral scales; no precloacal groove nor depression; median row of transversely enlarged subcaudal scales; a complete nuchal loop; and a dorsal pattern consisting of three long dark brown bands, one above shoulders and two above abdomen.